2014
DOI: 10.1007/s10517-014-2459-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Leptin and Ghrelin in Induction of Differentiation of IL-17-Producing and T-Regulatory Cells

Abstract: We studied isolated and combined effects of leptin and ghrelin on the formation of IL-producing and T-regulatory cells. Leptin in concentrations comparable with its normal blood concentration during pregnancy (trimester II-III) promotes differentiation of peripheral blood CD4(+) cells to IL-17-producing cells and enhances IL-17A production, but suppresses the formation of T-regulatory cells in vitro. In contrast, ghrelin in a concentration typical of trimester I-II of pregnancy reduces the number of IL-17-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…18 Several recent studies also reported the positive role of leptin or leptin receptor in Th17 differentiation. [24][25][26] However, Moraes's study found that leptin decreases CD4+ Foxp3+ and CD4 + IL-17+ cell frequency in the draining lymph nodes of immunized mice but increases subsequent delayed-type hypersensitivity responses. 27 This discrepancy may arise from different experimental condition and definition of CD4+ T cells in different studies.…”
Section: Discussionmentioning
confidence: 98%
“…18 Several recent studies also reported the positive role of leptin or leptin receptor in Th17 differentiation. [24][25][26] However, Moraes's study found that leptin decreases CD4+ Foxp3+ and CD4 + IL-17+ cell frequency in the draining lymph nodes of immunized mice but increases subsequent delayed-type hypersensitivity responses. 27 This discrepancy may arise from different experimental condition and definition of CD4+ T cells in different studies.…”
Section: Discussionmentioning
confidence: 98%
“…In line with the finding that GHSR was required for the ability of ERM to upregulate DEL-1, ghrelin also enhanced DEL-1 expression and exerted a similar antiinflammatory effect as ERM in the lungs after intratracheal challenge with a sublethal dose of LPS. Similar to DEL-1, which is a potent antagonist of IL-17 induction (13,17,18,20,21), ghrelin was earlier shown to inhibit IL-17 responses (41,42). Future studies are warranted for a better understanding of the potential relationship between DEL-1 and ghrelin in regulating IL-17 responses and how they might antagonize leptin, which promotes Th17 differentiation and IL-17 production (42,43).…”
Section: Figure 5 Erm Reverses Il-17-mediated Suppression Of Del-1 Bmentioning
confidence: 99%
“…In collagen-induced arthritis mouse model, articular injection of leptin (5 μg) increased the number of Th17 in the joint tissue, resulting in exacerbating joint inflammation, and consequently early onset of arthritis and increased disease severity ( Deng et al, 2012 ). Leptin, in concentrations similar to that found in blood during pregnancy, promoted the differentiation of peripheral blood CD4+ cells to Th17 cells, but suppressed the formation of Treg cells in vitro ( Orlova and Shirshev, 2014 ). CD4+ T cell-derived leptin, but not plasma leptin, were positively correlated with the percentage of Th17 cells or RORγt levels in chronic lymphocytic thyroiditis, an organ-specific autoimmune disease ( Wang et al, 2013 ).…”
Section: Leptin and Adaptive Immunity ( Figure mentioning
confidence: 99%